Transnationalism in the Prussian East - Tilse, M. author. aut Link
XIII, 289 p.
Keywords: Interpreting the German-Polish relationship according to a paradigm of 'synthesis' between nations, this book examines the process and socio-political effects of how conflict and contradiction between Germans and Poles gave rise to mentalities and behaviours that were 'transnational'; representing the harmonization of the national dichotomy.